2014
DOI: 10.1128/aem.03161-13
|View full text |Cite
|
Sign up to set email alerts
|

Intimin Gene ( eae ) Subtype-Based Real-Time PCR Strategy for Specific Detection of Shiga Toxin-Producing Escherichia coli Serotypes O157:H7, O26:H11, O103:H2, O111:H8, and O145:H28 in Cattle Feces

Abstract: g Shiga toxin-producing Escherichia coli (STEC) strains belonging to serotypes O157:H7, O26:H11, O103:H2, O111:H8, and O145:H28 are known to be associated with particular subtypes of the intimin gene (eae), namely, ␥1, ␤1, , , and ␥1, respectively. This study aimed at evaluating the usefulness of their detection for the specific detection of these five main pathogenic STEC serotypes in cattle feces. Using real-time PCR assays, 58.7% of 150 fecal samples were found positive for at least one of the four targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…The proportion of isolation assays leading to the isolation of one of the top five STEC strains was relatively low, as previously observed in various studies (14,15,17). The reasons for this discrepancy, including PCR-based strategy and isolation assays limitations, have been already discussed elsewhere (26,(40)(41)(42). In this study, three isolation procedures were used in parallel and allowed us to improve the isolation fraction of the top five STEC strains.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The proportion of isolation assays leading to the isolation of one of the top five STEC strains was relatively low, as previously observed in various studies (14,15,17). The reasons for this discrepancy, including PCR-based strategy and isolation assays limitations, have been already discussed elsewhere (26,(40)(41)(42). In this study, three isolation procedures were used in parallel and allowed us to improve the isolation fraction of the top five STEC strains.…”
Section: Discussionmentioning
confidence: 59%
“…The PCR-based strategy used to detect suspect samples was that described in the ISO 13136:2012 technical specification, to which we added a screening of the eae subtypes associated with the five major EHEC (11,26). Indeed, we previously showed that this additional screening step helped to be more discriminating for the specific detection of suspect samples likely to contain the five major STEC in cattle feces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen types and nine subtypes of the eae gene, namely, ␣, ␣2, ␤1 to ␤3, ␥1, ␥2, ␦, ε, ε2 to ε4, , , 2, , , 2, , , , , , , , , and , have been deposited in the GenBank database (14). The eae subtypes are responsible for some host tissue cell tropisms (15) and are related to human infections; eae subtypes ␤, ␥, ε, and are those most frequently associated with human infections (16,17).…”
mentioning
confidence: 99%